2012
DOI: 10.1037/a0025738
|View full text |Cite
|
Sign up to set email alerts
|

Elevated responding to safe conditions as a specific risk factor for anxiety versus depressive disorders: Evidence from a longitudinal investigation.

Abstract: The current study evaluated the degree to which startle reflexes (SRs) in safe conditions versus danger conditions were predictive of the onset of anxiety disorders. Specificity of these effects to anxiety disorders was evaluated in comparison to unipolar depressive disorders and with consideration of level of neuroticism. A startle paradigm was administered at baseline to 132 nondisordered adolescents as part of a longitudinal study examining risk factors for emotional disorders. Participants underwent a repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 56 publications
10
117
0
1
Order By: Relevance
“…More precisely, the ability to maintain discrimination between aversive and safe cues under aversive circumstances is crucial to long-term remission and/or resilience and consequently for the prevention of relapse. Deficits in discrimination are in fact described as a hallmark of anxiety-and stress-related disorders (Grillon et al, 2008;Lissek et al, 2009Lissek et al, , 2013Jovanovic et al, 2012;Duits et al, 2015) and are predictive of resilient responding to stress (Craske et al, 2013). In support of this, anxiety patients are characterized by more shallow generalization gradients as compared to controls (Duits et al, 2015).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…More precisely, the ability to maintain discrimination between aversive and safe cues under aversive circumstances is crucial to long-term remission and/or resilience and consequently for the prevention of relapse. Deficits in discrimination are in fact described as a hallmark of anxiety-and stress-related disorders (Grillon et al, 2008;Lissek et al, 2009Lissek et al, , 2013Jovanovic et al, 2012;Duits et al, 2015) and are predictive of resilient responding to stress (Craske et al, 2013). In support of this, anxiety patients are characterized by more shallow generalization gradients as compared to controls (Duits et al, 2015).…”
Section: Discussionmentioning
confidence: 75%
“…Whether ROF is differential or generalized is however of critical clinical importance, as the ability to discriminate safety from threat cues is negatively associated with pathological anxiety (Lissek et al, 2005;Duits et al, 2015) and predictive of resilient responding to life stress (Craske et al, 2013). Consequently, the ability to maintain discrimination under aversive circumstances might critically underlie longterm remission and/or resilience.…”
Section: Introductionmentioning
confidence: 99%
“…These effects may be related specifically to citalopram's anxiolytic effects, and both heightened startle response and negative attentional biases have been related more consistently to anxiety than depression [50,51] (see §4b for more details on distinguishing between the anxiolytic and antidepressant effects of SSRIs).…”
Section: (I) Short-term Administrationmentioning
confidence: 99%
“…While some of the studies also observed, to a certain degree, enhanced responding to the CS2 despite a more pronounced enhancement for the CS+ (Milad et al 2005;Dirikx et al 2007b;Kull et al 2012), other studies demonstrate ROF to both CS+ and CS2 to the same degree (generalized reinstatement). Whether ROF is specific for the CS+ or generalized to the CS-(s) is important, since the ability to discriminate safety cues from threat cues is negatively associated with pathological anxiety (Lissek et al 2005) and predictive of resilient responding to life stress (Craske et al 2012) (also see the section "Self-reported anxiety" below). Furthermore, it's not the mere enhancement of responses (observed in both differential and generalized reinstatement), but the ability to maintain a discrimination under aversive circumstances which might critically underlie long-term remission and/or resilience.…”
Section: Reinstatement In Humansmentioning
confidence: 99%